Reliability of specific on-ice repeated-sprint ability test for ice-hockey players - Karel Hůlka; Jan Bělka; Roman Cuberek; Ondřej Schneider (Palacký University Olomouc, 2014)
Background: Repeated sprint ability tests are today widely used to evaluate the performance capability in team sports. Objective: The aim of this study was to determine the reliability of a specific ice hockey test, which indicates the agility and repeated-sprint ability of the players. Methods: Twenty four highly trained junior ice hockey players (age = 17.68 ± 1.52 years; BMI = 23.8 ± 1.92 kg . m-2) participated in the study. Each participant was assessed for specific on-ice repeated-sprint ability test 12 × 54 m with 30 s rest. Intraclass correlation coefficient (association between two repeated measurements) and coefficient of variation were calculated to assess the reliability of the test. Results: All intraclass correlation coefficients were .78 for sprint decrement and .98 for total time and the best time, the coefficient of variation was 1.52% for best sprint time, 1.31% for total time and 19.3% for sprint decrement variable. Conclusions: The results suggest the high reliability of the ice hockey agility test expressed by the best sprint time and repeated-sprint ability by the total time and less reliability of sprint decrement.